PENGARUH KEGIATAN OUTBOUND TERHADAP KEMAMPUAN SOSIAL EMOSIONAL PADA ANAK USIA 5-6 TAHUN DI TK BINTANG CERIA KOTA PEKANBARU - Wulansari, Amalia; Zulkifli N, Zulkifli N; Kurnia, Rita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research is an experimental study using the design of one group pretest posstest desaign. This study aims to determine the emotional and social abilities of children aged 5-6 years before and after applying outbound activities in Kindergarten Bintang Ceria Pekanbaru city, and to determine the magnitude of the influence of outbound activities to improve the emotional and social abilities of 5-6 year olds in Kindergarten Bintang Ceria Pekanbaru city. The sample used in this study was 20 people. The data collection technique used is observation. Data analysis techniques using the t-test using SPSS 16.0 program. The pretest results were obtained with the number 164 with an average of 8.2. Then experimenting with the use of outdoor visual media, then looking at the posttest results obtained with a value of 300 with an average of 15. It can be seen that after the treatment (emotional treatment) the emotional social ability has a significant increase that there are no children who are at BB or 0 criteria %, which is in the MB category as many as 4 people with a percentage of 20%, and children in the BSB category as many as 10 people with a percentage of 50%, children in the BSH category as many as 6 people with a percentage of 30%. Through a two-party test, it can be seen that there are significant differences before and after the outbound treatment of the social emotional abilities of children aged 5-6 years in Kindergarten Bintang Ceria Pekanbaru City. This can be seen from the t count more days t table (6.825 ˃ 2.093). Thus Ho is rejected and Ha is accepted. This has the meaning that there are differences in the development of the ability of significant differences before and after the outbound treatment of the emotional social abilities of children.Keywords: Outbound, Emotional Social Ability